The CTLA-4 rs231775 GG genotype is associated with favorable 90-day survival in Caucasian patients with sepsis. Issue 1 (December 2018) - Mewes, Caspar; Büttner, Benedikt; Hinz, José; Alpert, Ayelet; Popov, Aron; Ghadimi, Michael; Beissbarth, Tim; Tzvetkov, Mladen; Shen-Orr, Shai; Bergmann, Ingo; Mansur, Ashham
Abstract Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) is a surface protein on T cells, that has an inhibitory effect on the host immune reaction and prevents overreaction of the immune system. Because the functional single-nucleotide polymorphism (SNP) rs231775 of the CTLA-4 gene is associated with autoimmune diseases and because of the critical role of the immune reaction in sepsis, we intended to examine the effect of this polymorphism on survival in patients with sepsis. 644 septic adult Caucasian patients were prospectively enrolled in this study. Patients were followed up for 90 days. Mortality risk within this period was defined as primary outcome parameter. Kaplan-Meier survival analysis revealed a significantly lower 90-day mortality risk among GG homozygous patients (n = 101) than among A allele carriers (n = 543; 22% and 32%, respectively; p = 0.03565). Furthermore, the CTLA-4 rs231775 GG genotype remained a significant covariate for 90-day mortality risk after controlling for confounders in the multivariate Cox regression analysis (hazard ratio: 0.624; 95% CI: 0.399–0.975; p = 0.03858). In conclusion, our study provides the first evidence for CTLA-4 rs231775 as a prognostic variable for the survival of patients with sepsis and emphasizes the need for further research to reveal potential functional associations between CTLA-4 and the immune pathophysiology of sepsis.